2022
DOI: 10.1080/07853890.2021.1993327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of colchicine on mortality and morbidity in COVID-19: a systematic review

Abstract: Introduction Colchicine, because of its anti-inflammatory and possible anti-viral properties, has been proposed as potential therapeutic option for COVID-19. The role of colchicine to mitigate “cytokine storm” and to decrease the severity and mortality associated with COVID-19 has been evaluated in many studies. Objective To evaluate the role of colchicine on morbidity and mortality in COVID-19 patients. Methods This systematic review was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…With regard to the data from systematic reviews and meta-analyses, including randomized clinical trials and observational studies, regarding the use of colchicine in COVID-19, controversial results have been reported, mostly due to the number and type of articles included at different times during the COVID-19 pandemic. While several meta-analyses of randomized clinical trials [ 52 55 ] and observational studies [ 56 , 57 ] have provided negative or inconclusive results regarding the role of colchicine in COVID-19 mortality, a higher number of these studies found positive effects of colchicine in terms of reduction of hospital admissions [ 52 ], hospitalization time [ 58 ], and mortality [ 53 , 54 , 59 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the data from systematic reviews and meta-analyses, including randomized clinical trials and observational studies, regarding the use of colchicine in COVID-19, controversial results have been reported, mostly due to the number and type of articles included at different times during the COVID-19 pandemic. While several meta-analyses of randomized clinical trials [ 52 55 ] and observational studies [ 56 , 57 ] have provided negative or inconclusive results regarding the role of colchicine in COVID-19 mortality, a higher number of these studies found positive effects of colchicine in terms of reduction of hospital admissions [ 52 ], hospitalization time [ 58 ], and mortality [ 53 , 54 , 59 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 – 10 ]. Recent studies showed that colchicine is potential to prevent Covid-19 complications [ 11 , 12 ]. Colchicine consists of a trimethoxy benzene ring (A-ring), a seven-membered ring (B-ring) with an acetamide group, and a methoxy tropone ring (C-ring) in molecule.…”
Section: Introductionmentioning
confidence: 99%
“… 8 The results of randomised trials of colchicine and antithrombotic therapies in patients with COVID-19 have been inconclusive and additional data are required to clarify their role. 9 , 10 Aspirin and rivaroxaban are effective antithrombotic drugs when used alone or in combination in patients with cardiovascular disease, 11 , 12 but the combination has not been tested in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%